Kajian Bentuk dan Motif Ornamen pada Bangunan Cagar Budaya di Kota Bandung : Studi Kasus : GPIB Bethel Bandung - Adinda Leoni Osami Musa; Kania Hasna Zain; Locita Prajna; Vanessa Nur Fatimah Azzahra (Program Studi Arsitektur Fakultas Teknik Universitas Mataram, 2023)
A building certainly has its own philosophy and meaning which can be seen from the shape and details of the building elements. The unique shape of the building becomes an architectural value that invites to be studied because of its visually attractive appearance. But not infrequently architectural values ​​are implied in the architectural details of a building. Of the many historical heritages in the city of Bandung, GPIB Bethel Bandung is a historical building that is more than 50 years old. Bethel GPIB is a class A cultural heritage building. A cultural heritage building is a building that has architectural characteristics both in terms of architectural value, aesthetics and represents a cultural symbol. Apart from having history, Bethel GPIB also has architectural values ​​and implicit and explicit meanings in every element of its building. In this journal, the architectural meaning of the GPIB Bethel Bandung building is written, information obtained from the survey results to the location and the results of interviews with GPIB Bethel Bandung. The data obtained were identified and studied using qualitative and descriptive research methods with the aim of knowing more about the meaning and philosophy.